Effects of soil and water conservation practices on selected soil physico-chemical properties in Debre-Yakob Micro-Watershed, Northwest Ethiopia - Alemayehu, Tigest; Fisseha, Getachew (Ethiopian Journal of Science and Technology, 2025)
Although different types of soil and water conservation practices (SWCPs) were introduced, the sustainable use of these practices is far below expectations, and soil erosion continues to be a severe problem in Ethiopia. Therefore, this study was conducted at Debre Yakobe Micro-Watershed (DYMW), Northwest Ethiopia with the general objective of finding out the effects of SWCPs on selected soil physico-chemical properties. Practices including non-conserved plot in the gentle slope (NCGS), non-conserved plot in the moderate slope (NCMS), bund with Sesbania sesban in the gentle slope (BSGS), bund with Sesbania sesban in the moderate slope (BSMS), bund with pigeon pea (Cajanus cajan) in the gentle slope (BPGS) and bund with pigeon pea in the moderate slope (BPMS) were examined. Soil samples were collected from different land management plots and soil texture while bulk density (BD), pH, organic matter (OM), total nitrogen (TN), Available Phosphors (Av.P), and cation exchange capacity (CEC) were analyzed in the laboratory. Data were analyzed with the use of one-way analysis of variance and simple regression methods. The results of the study revealed that there is significant difference (p< 0.05) between conserved and non-conserved plots. The conserved plots had the highest soil pH (BPMS) 6.7, OM (BPMS) 3.01%, TN (BSGS) 0.13%, Av.P (BPMS) 4.20 (ppm) and CEC (BSGS) 32.01 cmol(+) kg-1 but a lower BD (BPMS) 1.34 g cm-3; suggesting that bund accompanied by Sesbania sesban and pigeon pea were found to be effective in improving soil physico-chemical properties in the study area.